Physics for chemists - Ozerov, R. P. (Ruslan Pavlovich), 1926- (Elsevier, 2007)
The development of science, technology and industry in the near future requires new materials and devices, which will differ in many aspects from that of past years. This is due to the fact that many sophisticated processes and new materials are being invented. The computer engineering field is a typical example. The main building block for these achievements is science, and leading it is physics, which provides the foundation for the chemical, biological and atomic industries. Physics for Chemists contains many instructive examples complete with detailed analysis and tutorials to evaluate the student's level of understanding. Specifically it is focused to give a robust and relevant background to chemistry students and to eliminate those aspects of physics which are not relevant to these students. This book is aimed at chemistry students and researches who would by using the book, not only be able to perform relevant physical experiments, but would then also be in a position to provide a well founded explanation of the results. * Fundamental principles of modern physics are explained in parallel with their applications to chemistry and technology * Large number of practical examples and tasks * Presentation of new aspects of chemical science and technology e.g. nanotechnology and synthesis of new magnetic materials.